Pemahaman Umat Tentang Sakramen Pengurapan Orang Sakit di Stasi Santo Fransiskus Xaverius Klabat, Paroki Santo Fransiskus de Sales Kokoleh - Yudhi Geraldy Moningka; Adrianus Dalia; Bernadina Waha Labuan (Jurnal Penelitian Pendidikan Agama Katolik, 2024)
The sacrament of the anointing of the sick is a significant aspect of the Catholic faith, yet there is a lack of understanding among some believers. This prompted a study to assess the comprehension of the sacrament among the churchgoers of Fransiskus Xaverius Klabat Outpost, St. Fransiskus de Sales Kokoleh Parish, and explore ways to enhance their understanding. The study utilized qualitative research methods, including observation, interviews, and documentation studies, with data sourced from the St. Fransiskus Xaverius Klabat Outpost. The findings revealed that the sacrament is intended to provide healing and strength from God to those who are ill, with the priest responsible for preparing holy oil, blessing water, and a prayer formula, and the recipient expected to have candles, crosses, water, salt, and a readiness to receive the sacrament. The graces of the sacrament include healing, strength, and forgiveness of sins. Pastoral efforts, such as brief catechesis, are being implemented to help people understand the meaning, purpose, essential elements, and fruits of the sacrament of anointing the sick.